First Demonstration of Magnetoelectric Coupling in a Polynuclear Molecular Nanomagnet: Single‐Crystal EPR Studies of [Fe3O(O2CPh)6(py)3]ClO4⋅py under Static Electric Fields - Boudalis, Athanassios K.; Robert, Jérôme; Turek, Philippe (Chemistry : a European journal, 2018)
Single‐crystal EPR experiments show that the highly symmetric antiferromagnetic half‐integer spin triangle [Fe3O(O2CPh)6(py)3]ClO4⋅py (1, py=pyridine) possesses a ST=1/2 ground state exhibiting high g‐anisotropy due to antisymmetric exchange (Dzyaloshinskii–Moriya) interactions. EPR experiments under static electric fields parallel to the triangle's plane (i.e., perpendicular to the magnetic z‐axis) reveal that this ground state couples to externally applied electric fields. This magnetoelectric coupling causes an increase in the intensity of the intradoublet EPR transition and does not affect its resonance position when B0∥z. The results are discussed on the basis of theoretical models correlating the spin chirality of the ground state with the magnetoelectric effect. Clear! An electric field applied on the antiferromagnetic spin‐chiral complex [Fe3O(O2CPh)6(py)3]ClO4⋅py couples to the spin of its ground state and modifies its Electron Paramagnetic Resonance (EPR) spectrum. This magnetoelectric coupling can provide electric control of the spin states of Molecular Nanomagnets.